Questionnaire development on measuring parents’ anxiety about their children’s education: Empirical evidence of parental perceived anxiety data for primary and secondary school students in China - Sun, Jiangjie; Liu, Tong; Gao, Yufei; Li, Hui; Chen, Yao; Diao, Haibao; Zhang, Genfa; Shen, Hui; Chang, Rong; Yu, Zhenliang; Lu, Jingru; Liang, Liang; et al. (Frontiers in Psychology, 2022)
Background: With the implementation of the "double reduction" policy in China, parents of primary and secondary school students are experiencing a growing trend of educational anxiety that needs to be alleviated. Objective: To manage the education anxiety risk of parents of primary and secondary school students, a measurement questionnaire of parents' anxiety about their children's education (MQPAE) was developed and its reliability and validity were evaluated. Methods: A self-administered MQPAE was developed. An online crowdsourcing questionnaire platform was used to collect data on parents' anxiety about their children's education (PAE), and parents of primary and secondary school students in Hefei, China, were selected as the study population. The randomly extracted 5747 questionnaires were gradually screened by discrete trend method, T-test, and Pearson's correlation coefficient method for the initial screening of PAE items, based on which exploratory factor analysis was conducted for the final screening of questionnaire items and the reliability of the questionnaire. The reliability of the questionnaire was assessed by internal consistency and Pearson's correlation coefficient analysis. A validation factor analysis was conducted using 639 pre-selected data to investigate the validity of the questionnaire. Structural equation modeling was used to investigate the structural validity of the questionnaire, and average variance extracted (AVE), combined reliability (CR) , and maximum of shared squared variance (MSV) were used to test for convergent and discriminant validity. Results: Exploratory factor analysis extracted 5 factors with a cumulative variance contribution of 65.66%. The validation factor analysis showed that 2/df=4.306, CFI=0.920, NFI=0.898, RMSEA=0.072＜0.08, AGFI=0.839＞0.80, PNFI=0.793 and PGFI=0.708. The overall Cronbach'sαcoefficient of the questionnaire was 0.956, and the factors’ Cronbach'sαcoefficients were 0.926, 0.857, 0.913, 0.901, and 0.768 respectively. Repeated measurements of Pearson correlation coefficients were 0.908, 0.911, 0.873, 0.891, 0.907 and 0.885 (all P < 0.001). The AVE was greater than 0.5 and the CR was greater than 0.7, and the value of the MSV was less than the corresponding AVE. Conclusion: The MQPAE has good reliability and validity and can be used in studies related to PAE of primary and secondary school students.